2013
DOI: 10.1002/aoc.3016
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐free CuI‐catalyzed coupling and cyclization of β‐bromo‐α,β‐unsaturated amides with formamide leading to pyrimidinones

Abstract: β-Bromo-α,β-unsaturated amides were coupled and cyclized with formamide in DMF at 100°C in the presence of a catalytic amount of a copper(I) salt along with a base to give the corresponding pyrimidinones in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…The high resolution mass spectrum of 3m shows peak at m/z ¼ 272.0835 (Mþ, 100% intensity). Similar dehydrogenation was observed by our recent report on the coupling and cyclization of b-bromo-a,b-unsaturated amides with formamide [9]. The configuration of stereoisomeric product 3m was clarified by quantum chemical calculations compared with observed NMR chemical shifts.…”
Section: Resultssupporting
confidence: 79%
“…The high resolution mass spectrum of 3m shows peak at m/z ¼ 272.0835 (Mþ, 100% intensity). Similar dehydrogenation was observed by our recent report on the coupling and cyclization of b-bromo-a,b-unsaturated amides with formamide [9]. The configuration of stereoisomeric product 3m was clarified by quantum chemical calculations compared with observed NMR chemical shifts.…”
Section: Resultssupporting
confidence: 79%
“…[37] Product 3b was chosen for structural identification and confirmed from its IR, mass, 1 H NMR and 13 C NMR spectra. Similar dehydrogenation was observed in our recent work on the coupling and cyclization of β-bromo-α,β-unsaturated amides with formamide.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13][14][15][16][17][18][19] β-Bromo-α,β-unsaturated aldehydes and their derivatives are readily prepared from α-methylene group-containing ketones by bromination under Vilsmeier-Haack conditions [20,21] and subsequent transformation, and the products can serve as valuable building blocks for the construction of various cyclic compounds. [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Among such carbonlative cyclization reactions, we recently have shown that β-bromo-α,β-unsaturated carboxylic acids can be carbonylatively cyclized with 2,2-dimethylhydrazine under carbon monoxide pressure in the presence of a palladium catalyst to give 1-(dimethylamino)-1H-pyrrole-2,5-diones. [39] The present work arose during the course of the application of this protocol to the reaction with arylhydrazines.…”
Section: Introductionmentioning
confidence: 99%
“…The isolation of pure products was carried out via thin layer (silica gel 60 GF 254 , Merck) chromatography. The starting β‐bromo‐α,β‐unsaturated amides were synthesized via three steps from the corresponding ketones according to literature procedures, and all are known . Commercially available organic and inorganic compounds were used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…Among such heterocyclic compounds, we also have shown two examples for the synthesis of pyrimidinone scaffold. It is reported that β‐bromo‐α,β‐unsaturated amides are coupled and cyclized with formamide in the presence of CuI and a base without an additional ligand to give pyrimidinones . Such a similar coupling and cyclization leading to pyrimidinones is also exemplified by the reaction of β‐bromo‐α,β‐unsaturated carboxylic acids and amidine hydrochlorides in the presence of copper powder under microwave irradiation conditions .…”
Section: Introductionmentioning
confidence: 95%